Share Transfer Limitations for Joint Stock Companies and Companies in Regulated Sectors With a Special Focus on the Energy Market - Hayri Bozgeyik; Beşir Fatih Doğan; Temel Güner (İstanbul Hukuk Mecmuası)
There is a principal freedom of share transfer in joint stock companies where partners can leave the company only by transferring shares. According to this principle, partners can freely transfer their shares to anyone they want at any time without the need for permission or approval from any individual, organ, or institution. However, some exceptions have been made to this rule for joint stock companies operating in regulated markets, such as banking and insurance, and permission from the authority that regulates and supervises the market is required to transfer shares. In this context, the energy market is one of the markets whose share transfer is subject to the permission of the competent authority. To transfer shares in joint stock and limited companies operating in the energy market, permission from the Energy Market Regulatory Authority (EMRA) must be obtained. This paper examines the share transfer restrictions in companies operating in the energy market and the situations in which EMRA permission is required for share transfers.